Enhancing the nonlinear thermoelectric response of a correlated quantum dot in the Kondo regime by asymmetrical coupling to the leads - Perez Daroca, Diego Raul (2018)
We study the low-temperature properties of the differential response of the current to a temperature gradient at finite voltage in a single-level quantum dot including electron-electron interaction, nonsymmetric couplings to the leads, and nonlinear effects. The calculated response is significantly enhanced in setups with large asymmetries between the tunnel couplings. In the investigated range of voltages and temperatures with corresponding energies up to several times the Kondo energy scale, the maximum response is enhanced nearly an order of magnitude with respect to symmetric coupling to the leads.